Reproductive biology of the Amazonian amphibian fish the splash tetra Copella arnoldi with emphasis to histological characterization - Cordeiro, Jhennifer Gomes; Rodrigues, Jeane; dos Santos, Raquel; da Silva Rodrigues, Maira [UNESP]; Nóbrega, Rafael Henrique [UNESP]; da Silva Siqueira, Felipe Fernando; Maximino, Caio; de Siqueira-Silva, Diógenes Henrique (Wiley, 2022)
This study describes important components of the reproductive biology of the Amazonian amphibian fish Copella arnoldi. The species sex ratio biased to female 1.8 to 1 male and the length-weight relationship also shown differences between sexes (b value = 1.854 for females and 2.235 for males), although both presented allometric growth (b < 3), “being lighter for its length”. The results also show the importance of the histological analysis to describe the gametogenesis and, consequently, define the reproductive cycle of a fish species. It showed both, males and females, spawning capable during a whole year, whereas the gonadosomatic index pointed spawning capable females during the winter and summer, and spawning capable males only in the autumn. The species presents the rare type of semicystic spermatogenesis and the spermatids complete their differentiation into the tubular lumen, forming a Type I spermatozoa. Both the characteristics are described for the first time for the Lebiasinidae family. Such data can contribute to the discussions about the position of the Lebiasinidae family within the Characiform order, which still does not have a conclusion. Moreover, understand the reproductive biology of a fish species helps its preservation in its habitat and may be applied in restoration programs.
Keywords: fish reproduction; Lebiasinidae; oogenesis; reproductive cycle; spermatogenesis